Two new species of Lobellini from Central-South China (Collembola: Neanuridae) - Hu, Ya-Hui; Jiang, Cheng; Jiang, Ji-Gang; Jiang, Ji-Gang (Zootaxa, 2019)
Four species of the tribe Lobellini (Collembola: Neanuridae: Neanurinae) are recorded from Langshan National Geopark, Hunan Province, Central-South China. Two of them, Crossodonthina langshanensis sp. nov. and Lobellina gladius sp. nov., are new to science and described in this paper. Crossodonthina langshanensis sp. nov. is characterized by 2+2 black eyes on head; labral chaetotaxy as 2/4, 2; cephalic chaeta O present; mandible with 2 teeth and 2 fringed rami; maxilla outer lamella with filaments on inner edge. Lobellina gladius sp. nov. can be recognized by mandible with six teeth, cephalic chaeta O present and included in tubercle Fr, non-cross type chaetotaxy on cephalic posterior area, cephalic lateral tubercle Dl, L and So independent, Ant. I with 9 chaetae, Th. I with 4+4 tubercles, VT with 6–8 (usually 7) chaetae. New localities of Crossodonthina choui Jiang & Zhang, 2012 and Lobellina yinae Jiang, Huang & Luan, 2018 are also provided.